2023
DOI: 10.1002/ijc.34505
|View full text |Cite
|
Sign up to set email alerts
|

Transient Kupffer cell depletion and subsequent replacement by infiltrating monocyte‐derived cells does not alter the induction or progression of hepatocellular carcinoma

Abstract: Due to a combination of rapid disease progression and the lack of curative treatment options, hepatocellular carcinoma (HCC) is one of the deadliest cancers worldwide. Infiltrated, monocyte‐derived, tumor‐associated macrophages are known to play a role in HCC pathogenesis, but the involvement of Kupffer cells (KCs) remains elusive. Here, we used the Clec4F‐diphteria toxin receptor transgenic mouse model to specifically investigate the effect of KC depletion on HCC initiation, progression and neoplastic growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(101 reference statements)
1
3
0
Order By: Relevance
“…Several studies have demonstrated that human KCs can be identified on RNA level by expression of MARCO, CD5L, VSIG4 and TIMD4 21,[44][45][46][47] . Our scRNA-seq analysis of chemotherapytreated HB shows that TAMs have low MARCO expression and upregulated inflammatory markers, similar to transcriptional profiles of inflammatory monocyte-derived macrophages identified in several liver disease settings 30,[46][47][48][49][50] . Surprisingly, we find that TAMs express KC markers (CD5L, VSIG4, TIMD4) and display high tissue residency scores in HB.…”
Section: Discussionsupporting
confidence: 72%
“…Several studies have demonstrated that human KCs can be identified on RNA level by expression of MARCO, CD5L, VSIG4 and TIMD4 21,[44][45][46][47] . Our scRNA-seq analysis of chemotherapytreated HB shows that TAMs have low MARCO expression and upregulated inflammatory markers, similar to transcriptional profiles of inflammatory monocyte-derived macrophages identified in several liver disease settings 30,[46][47][48][49][50] . Surprisingly, we find that TAMs express KC markers (CD5L, VSIG4, TIMD4) and display high tissue residency scores in HB.…”
Section: Discussionsupporting
confidence: 72%
“…NOX enzymes were the principal source of ROS. NOX1 and secretion of IL-1α/β and TNF-α facilitated the advancement of hepatic fibrosis and inflammation (Amano et al, 2017;Sun et al, 2017;Vandierendonck et al, 2021). Targeting the phenotype of TAMs and the cytokines they secrete is the key to blocking the progression of the fibrotic liver into HCC (Table 1).…”
Section: Tams Have the Potential To Influence Invasion Migration And ...mentioning
confidence: 99%
“…Danger signals in HCC can activate the inflammatory regulation of KCs and promote drawing immune cells to the liver. The production of CCL2 by tumor cells leads to the absence of embryonic KCs in tissue and promotes the infiltration of monocyte-derived KCs and immature monocytes (M0) ( Thomann et al, 2021 ; Vanderborght et al, 2023 ). Myeloid precursor cells are recruited to infiltrate HCC, and the TME blocks its maturation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation